BERBAGAI WAKTU PENYIMPANAN SECARA SPEKTROFOTOMETRI UV-VIS - Ika Pramitha, Dewa Ayu; Suaniti, Ni Made; Suarsa, I Wayan (Jurnal Kimia (Journal of Chemistry), 2014)
This paper describes the determination of lamivudine content in pulveres by UV-Vis spectrophotometry. The purpose of this study was to determine the stability of lamivudine in various storage times. In this study, the validation of the method of the determination of lamivudine standard was also investigated with the following results: the linear regression equation y = 0.045x - 0.005 with correlation coefficient (r 2 ) of 0.9998. Furthermore the detection limits obtained was of 0.46 µg/mL, quantitation limit of 1.53 µg/mL, the coefficient of variation of 0.23%, accuracy of 3.59%, and the recovery was of 96.41%. The stability of lamivudine in the samples decreased during the observation period i.e. 0, 7, 14, 21, and 28 days, during which the contents of lamivudine obtained were 87.46%, 86.22%, 84.44%; 76, 87%, 79.38%, respectively.
Keywords: lamivudine, stability, pulveres, UV-Vis spectrofotomety